PYROXENITES AND CHROMITE MINERALIZATION OF THE SANGALYK SECTOR, SOUTHERN URALS - Salikhov D.N.; Belikova G.I.; Puchkov V.N.; Moroz T.N. (My University, 2007)
The nature of chromite ores is controversial. Previously, they were considered as products of the layering of ultramafic magma. A new hypothesis based on the genetic relation between chromites and secondary dunites has been proposed in recent works. The formation of secondary dunites is related to the partial melting of peridotites (more precisely, the pyroxene component of peridotites), resulting in the separation of primarily restitic dunites, an ore-bearing chromite portion, and a melt with a basalt (gabbro) composition. Thus, secondary dunites have a genetic relation with gabbro.